Consolidating medical ambulatory care services in the COVID-19 era - Aujayeb, Avinash; Johnston, Robert; Routh, Charlotte; Wilson, Patricia; Mann, Sandra (International Journal of Health Sciences, 2020)
The current covid-19 era is significant and unprecedented. There are significant challenges for re-organisation of care, re-distribution of resources and rationing of services for those with Covid-19.1,2 However, the wide array of non-covid-19 diagnoses are still presenting, albeit at lesser rates. We present the re-configuration of our Medical Ambulatory Care service (Same Day Emergency Care service) and hope that it can be applied to a certain extent across the United Kingdom (UK).